Flash array invalid block management - Jiao Xinquan; Zhu Zhenlin (Dianzi Jishu Yingyong, 2024)
Flash arrays play an important role in data storage today. The key to improve the reliability of Flash array is to propose a reasonable bad management method. For inherently bad blocks, the bad block management method based on integrated block and EEPROM lookup table are proposed. The burst bad block management method based on page skip and page replacement is proposed for the burst bad block management. The experimental analysis shows that the bad block management method improves the reliability of NAND Flash data storage and maximizes the utilization of NAND Flash storage space while ensuring the storage speed.